A MOOC-based flipped classroom: the pre-diploma students' perspectives / Imelia Laura Daneil ... [et al.] - Daneil, Imelia Laura; Tang Howe, Eng; Jacqueline, Susan Rijeng; Runggol, Christine Jacqueline (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The Massive open online course (MOOC) is a move toward greater openness in higher education. The current literature on MOOCs, covering research on their effectiveness to accommodate different students' abilities showed conflicting results in this regard. With limited studies on a MOOC-based flipped classroom in Malaysian higher education, this study explored the perceived usefulness and perceived ease-of-use of the MOOC-based flipped classrooms among the pre-diploma students who enrolled in the English MOOC. The pre-diploma students were interviewed to respond to these concerns. Questionnaires were also administered to all registered users to analyze the perceived use and ease-ofuse of the MOOCs when used in flipped classrooms. The study found the significant challenges faced by pre-diploma students in terms of the content, language, and technical aspects of MOOCs. Therefore, possible solutions to these challenges were identified and discussed. These findings can help the policy makers explore strategies for MOOC's future development, implementation, and success in the context of higher education in Malaysia specifically for pre-diploma students.